Phytochemical-Based In-Silico Study for Anti-Rabies Drug Discovery: A Pharmaceutical Perspective - Rashed Ahmed (RADINKA JOURNAL OF HEALTH SCIENCE, 2026)
Rabies continues to pose a formidable global health threat, particularly in regions burdened by limited access to vaccines and effective antiviral therapies. This study utilized a high-throughput in silico approach to evaluate the antiviral potential of specific phytochemical compounds against two critical targets of the rabies virus: the glycoprotein (G protein) and the RNA-dependent RNA polymerase (RdRp). Through integrated computational methods—including molecular docking, ADMET profiling, and molecular dynamics (MD) simulations—curcumin, quercetin, and epigallocatechin gallate (EGCG) were identified as primary therapeutic candidates. Molecular docking results revealed robust binding affinity to both target proteins, suggesting a dual-action mechanism capable of inhibiting both viral entry and replication. Furthermore, absorption, distribution, metabolism, excretion, and toxicity (ADMET) analysis indicated favorable pharmacokinetic profiles, characterized by high oral bioavailability and significant blood-brain barrier permeability; the latter is a decisive factor for treating neurotropic infections. Molecular dynamics simulations further validated the structural stability of these protein-ligand complexes under physiological conditions. Collectively, these findings offer a compelling theoretical foundation for developing cost-effective and sustainable anti-rabies interventions, providing a clear trajectory for subsequent in vitro and in vivo experimental validation.